2019
DOI: 10.1192/bjb.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physical health of adolescent in-patients in generic and secure services: retrospective case-note review

Abstract: Aims and methodTo assess physical health needs of adolescent in-patients by routine monitoring. A retrospective analysis of case notes was conducted on a 6-month intake to generic and secure adolescent mental health units in Greater Manchester, UK.ResultsFifty individuals were admitted (52% female, average age 15.84 years). Diagnoses varied and 66% were prescribed medications before admission. All had a physical health assessment, which identified various physical health risk factors. Average body mass index w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 27 publications
(44 reference statements)
2
25
0
Order By: Relevance
“… Psychosis Group = 81.5 days (sd 98.9) Non-Psychosis Group = 42.2 days (sd 60.5) Psychosis Group mainly schizophrenia (87.7%, n = 71); Non-Psychosis Group = conduct/ADHD (47.7%, n = 136), adjustment disorders (24.6%, n = 70), neurodevelopmental but hospitalized due to non-psychotic behavioral deterioration (15.1%, n = 43) Antispychotics for Psychosis Group 33.3% (n = 27), Non-Psychosis Group 33.7% (n = 93) Cross-sectional (Retrospective cohort) BMI, Weight, Tobacco Use 24.9% young people smoked and individuals with non-psychotic disorders had slightly higher average BMI scores than psychotic disorders (although both were within the healthy weight range). Carney et al, (2019) [ 19 ] UK Adolescent inpatients aged 13–18 in generic or secure mental health inpatient unit in the UK, presenting with a range of complex mental health needs which cannot be met safely within the community. 50 15.84 (sd 1.46) 52% female (n = 26), 48% male (n = 24) Mixed gender generic adolescent inpatient service providing evidence based treatments for young people with complex mental health needs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Psychosis Group = 81.5 days (sd 98.9) Non-Psychosis Group = 42.2 days (sd 60.5) Psychosis Group mainly schizophrenia (87.7%, n = 71); Non-Psychosis Group = conduct/ADHD (47.7%, n = 136), adjustment disorders (24.6%, n = 70), neurodevelopmental but hospitalized due to non-psychotic behavioral deterioration (15.1%, n = 43) Antispychotics for Psychosis Group 33.3% (n = 27), Non-Psychosis Group 33.7% (n = 93) Cross-sectional (Retrospective cohort) BMI, Weight, Tobacco Use 24.9% young people smoked and individuals with non-psychotic disorders had slightly higher average BMI scores than psychotic disorders (although both were within the healthy weight range). Carney et al, (2019) [ 19 ] UK Adolescent inpatients aged 13–18 in generic or secure mental health inpatient unit in the UK, presenting with a range of complex mental health needs which cannot be met safely within the community. 50 15.84 (sd 1.46) 52% female (n = 26), 48% male (n = 24) Mixed gender generic adolescent inpatient service providing evidence based treatments for young people with complex mental health needs.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies reported BMI values (n = 1731), ranging from 18.2–32.5 [ 19 , 28 , 29 , 33 , 34 , 39 , 40 , 44 , 48 , 56 ]. The weighted average was 23.96 (95% CI 22.79–25.13), and fell within the healthy weight range (18.5–24.9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They often present with risk factors for poor physical health which precede the onset of illness. For example, many have high BMI values on admission, which rapidly increase with duration of stay (Carney, Imran, Law, Folstad, & Parker, 2019). They also display pre-cursors to developing metabolic disorders and preventable physical health conditions, such as dysregulated blood metabolites and hyperprolactinemia (Carney et al, 2016;Carney et al, 2019;Cordes et al, 2017;Eapen et al, 2012;Vancampfort et al, 2017).…”
Section: Discussionmentioning
confidence: 99%